Elementary School Teachers’ Self-Efficacy Toward Teaching Writing - Amatullah, Ummu Fauziyyatun; Iswara, Prana Dwija (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
Writing is an essential aspect of language learning and for the language skills needs of elementary school students. However, the self-efficacy of elementary school teachers towards teaching writing is known by little. Teachers' self-efficacy towards teaching writing affects their perceptions and judgments, influencing instructional decisions during student learning activities. This study aimed to describe elementary school teachers’ self-efficacy in teaching writing in the classroom. This research was completed by a quantitative approach with a survey method of 13 elementary school teachers. The research’s results indicate that the self-efficacy of elementary school teachers on writing lessons is still not optimal. Almost all teachers (11 out of 13) were at the 61-70% self-efficacy in teaching writing. 1 out of 13 teachers has achieved 60% self-efficacy in learning to write along with the percentage of self-efficacy of elementary school teachers in teaching writing. And only one teacher who has a level of > 70% self-efficacy in learning to write. Changing writing practice in elementary school will require individualized instructional methods to meet student needs as well as the personal assessment of self-efficacy to ensure that beliefs do not hinder the delivery of effective instructional writing practices.